La relación sujeto-objeto en el pensamiento estético del joven Lukács - Ramírez, Alexis (2007)
In the context of Hungry, shaken by a deep crisis that reached all levels of social life, also cultural-artistic expressions, the author of the esthetic reflexions of young Lukács, and plan the discussion of the method that part of the article history, and consciousness of the class, which centers its analysis around the Hegelians category, maintains both problems and searches the resolution of the conscious reality.